Isu kehamilan luar nikah dalam kalangan remaja di Malaysia: satu tinjauan sorotan literatur - Siong, Reffina; Tharshini, N.K. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Unwed pregnancy is a global phenomenon that transgresses racial, religion, and age boundaries. Thus, this article is prepared to review the unwed pregnancy issue among teenagers in Malaysia. A literature review was conducted to obtain information in Elsevier, Sage, and Google Scholar databases regarding the risk factors and impact of unwed pregnancy among young teenagers. The risk factors contributing towards unwed pregnancy are weak family ties, massive technology development, peer influence, and low socioeconomic and educational status. Besides, the impact of unwed pregnancy is baby dumping, health-related issues for the teenagers and infant, financial problem, and conflict among family members. As an overall impact, the review is expected to provide significant implications to the family institutions, community members, and concerned parties to have an in-depth understanding on issues related to unwed teenage pregnancy in Malaysia.